Demographics and Incident Location of Gunshot Wounds at a Single Level I Trauma Center - Benton, Blair; Watson, David; Ablah, Elizabeth; Lightwine, Kelly; Lusk, Ronda; Okut, Hayrettin; Bui, Thuy; Haan, James M (Kansas Journal of Medicine, 2021)
Introduction:  Little is known surrounding the demographic and geospatial factors of firearm-related traumas in the Midwest Region.  The purpose of this study was to describe the overall incidence of firearm-related traumas and examine any racial/ethnic disparities that may exist.Methods:  A retrospective review was conducted of all patients 14 years or older who were admitted with a gunshot wound (GSW) to a Level I trauma center between 2016 and 2017. Results:  Forty-nine percent of patients were Caucasian, 26.5% African American, and 19.6% Hispanic/Latino.  Hispanic/Latino patients were the youngest (25.8 ± 8.8) and Caucasians were the oldest (34.3 ± 14.1, P = 0.002).  Compared to Caucasian patients, African American (42.0%) and Hispanic/Latino (54.1%) patients were more likely to be admitted to the intensive care unit (ICU) (P = 0.034) and experienced longer ICU lengths of stay (2.5 ± 6.3 and 2.4 ± 4.7, P = 0.031, respectively).  African American patients (96.0%) experienced more assaults while Caucasians were more likely to receive gunshot wounds accidentally (26.9%, P = 0.001).  More African American (86.0%) and Hispanic/Latino (89.2%) patients were injured with a handgun and Caucasians sustained the highest number of shotgun/rifle related injuries (16.1%, P = 0.012).  Most GSWs occurred in zip codes 67202, 67203, 67213, 67211, and 67214.  Geographical maps indicated that GSWs were concentrated in low-income areas and areas with high minority populations.                                                                                                                                                                                              Conclusions:  Racial differences were noted, however, unlike national trends, most of our patients were older Caucasian males.